MANAJEMEN PENDIDIKAN KARAKTER BERBASIS BUDAYA DI PONDOK PESANTREN ROUDLATUT THOLIBIN SIRAU KEMRANJEN BANYUMAS - Fauzi Al Muhtad; Rita Sulastini; Sri Handayani (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2022)
This study aims to determine how the management of culture-based character education at the Roudlotul Tholibin Islamic Boarding School in Sirau Kemranjen Banyumas. This study uses a qualitative method. The subjects of the research were the caregivers of the pesantren, the principal, the teacher, and the head of the student organization of the pesantren. Data were collected by interview, observation, and document analysis. The results obtained in this study are 1) character education planning is prepared following the vision, mission and goals: